1986
DOI: 10.1080/00337578608207466
|View full text |Cite
|
Sign up to set email alerts
|

Accurate determination of the parameters of the 292.4-eV resonance of 91Zr and the 301.1-eV resonance of 96Zr

Abstract: High-resolution transmission measurements of zirconium" metal samples have been carried out at ORELA using the 80-m flight path and an improved 6 Li-glass scintillation neutron detector. Four different thicknesses of the pura zirconium metal and one sample of zircalloy were used in four separate experiments. The transmission data for these samples were measured at room temperature, and one sample was cooled to liquid nitrogen temperature. These data were analyzed using the multilevel R-matrix computer code SAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…The present assignment of J ϭ 3 for the 292.5-eV s-wave resonance in 91 Zr is especially significant as it clarifies decades of conflict as shown in Table I. The present measurements confirm the J ϭ 3 assignment of Salah et al 8 for this resonance. Figure 2 contrasts the best fits possible with each J value.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The present assignment of J ϭ 3 for the 292.5-eV s-wave resonance in 91 Zr is especially significant as it clarifies decades of conflict as shown in Table I. The present measurements confirm the J ϭ 3 assignment of Salah et al 8 for this resonance. Figure 2 contrasts the best fits possible with each J value.…”
Section: Discussionsupporting
confidence: 85%
“…The spin assignment for this resonance has a conflicting history, as Table I shows. The most recent work is that of Salah et al 8 who found this to be an s-wave resonance with J ϭ 3. The historical work on the 301.1-eV p-wave resonance in 96 Zr was less extensive.…”
Section: Introductionmentioning
confidence: 99%